2006
DOI: 10.1590/s1516-31802006000500009
|View full text |Cite
|
Sign up to set email alerts
|

Unusual occipital condyles of the skull: an osteological study with clinical implications

Abstract: The present osteological study provides a detailed morphological description of unusual occipital condyles showing uneven and serrated surfaces and also displaying longitudinal and transverse grooves on the left and right sides respectively. The case study also discusses the clinical importance of such anomalies. Precise anatomical knowledge of the occipital condyles is important for any craniovertebral operative procedures such as resection of the occipital condyles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Spontaneous occipito-atlantal fusion, and anomalies of the occipital condyles (20) can cause changes in the biomechanics of the craniovertebral junction. In odontoid fracture or C1-C2 instability associated with rheumatoid arthritis, the occipito-atlantal fusion moves as a single unit, leading to more displacement of the odontoid process and more instability of the craniovertebral junction.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous occipito-atlantal fusion, and anomalies of the occipital condyles (20) can cause changes in the biomechanics of the craniovertebral junction. In odontoid fracture or C1-C2 instability associated with rheumatoid arthritis, the occipito-atlantal fusion moves as a single unit, leading to more displacement of the odontoid process and more instability of the craniovertebral junction.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional anatomy and surgery textbooks do not describe the anatomical variations in the OCs. Many such anomalies can be encountered incidentally [11].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that variations in shapes of the OC, as well as the measurements and incidence, have been reported in the previous clinical and anatomical studies, it has been observed during the dissection that the pattern of the OC in the CVJ was not as simple as it had been reported by many authors. [2345]…”
Section: Introductionmentioning
confidence: 99%